MORPHOMETRICAL STUDY OF LARVAL DEVELOPMENT OF CIRRHINA MIRIGALA (HAM.) REARED IN LABORATORY - RANI, RITA; GAUR, K.K.; TIWARI, VISHAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
The present investigation aimed at to study the morphological data of larval development reared to laboratoiy Conditions. Though larvae were reared in laboratory Conditions but a one month’s observatjoj made to evaluate the morphological readings of its larval development.